The Effect of Compulsory Mondok in Salafiyah Islamic Boarding Schools on The Success of Student Learning at PTKI - Barrulwalidin, Barrulwalidin (Institut Agama Islam Al-Aziziyah Samalanga, 2025)
This study aims to analyze the influence of the obligation of mondok in salafiyah pesantren on the success of student learning at Islamic Religious Universities (PTKI), especially at Al-Aziziyah Islamic University Indonesia (UNISAI). This research uses a qualitative approach with ethnographic methods. Data were obtained through participatory observation, in-depth interviews, and documentation studies of students who underwent mondok obligations at Dayah MUDI Mesjid Raya Samalanga. The results of the study show that the obligation of mondok has a positive impact on shaping student discipline, time management, and mental resilience. Structured cottage life encourages students to integrate spiritual and academic values in a balanced manner. Students not only gain a deeper understanding of religion, but also show improvements in academic performance. However, there were also several obstacles, such as double load pressure and schedule conflicts between campus and pesantren activities. This study recommends that PTKI and pesantren managers strengthen curriculum synergy and provide special assistance for monkok students. This integrative education model has proven to be able to form graduates who excel intellectually and spiritually.